Identifikasi Jenis dan Tingkat Serangan Hama Pada Pembibitan Tanaman Kelapa Sawit (Elaeis guineensi Jacq) di PT. Sentosa Kalimantan Jaya, Kabupaten Berau Provinsi Kalimantan Timur - Andi Nur Cahya; Iin Arsensi; Purwati Purwati (Agrifarm : Jurnal Ilmu Pertanian, 2019)
Identification of Types and Levels of Pests Attack on Palm Plantation Seedlings (Elaeis guineensis Jacq) at PT. Sentosa Kalimantan Jaya, Berau District East Kalimantan Province. Under the guidance of Iin Arsensi and Purwati. This study aims to determine the types of pests that attack oil palm seedlings, the frequency and intensity of oil palm pest attack on the Main Nursery stage nursery. The research was arranged in Survey method, determining 5 research plots in one block diagonally by marking on each plot with plastic marker of seeds, so obtained 15 research plots contained in 3 block that is block J, I and D. Each research plot consists of 30 Oil palm seedlings so that the number of observed 450 seeds of oil palm. The results showed that the types of pests that attack the oil palm seedlings in Main Nursery are Tungau (Tetranychus piercei), Adoretus compressus Beetle, and Locusta migratoria manilensis (Locusta migratoria manilensis); Block Frequency A pest attack in the category of minor attacks is 51.33%, 24% attack, while the intensity of pest attacks is a mild attack category; Frequency of Block I attack of pests in light attack category is 49,33%, moderate attack 37,33%, heavy attack 2%, while intensity of pest attack moderate attack category; Frequency of Block D attack of pest in light attack category is 41,3%, moderate attack 41,3%, severe attack 7,3%, while intensity of pest attack moderate attack category;